Incursions of southern-sourced water into the deep North Atlantic during late Pliocene glacial intensification - Lang, David; Bailey, Ian; Wilson, Paul; Chalk, Thomas; Foster, Gavin; Gutjahr, Marcus (Nature Geoscience, 2016)
International audience